Quantitative ethnobotanical exploration of wild medicinal plants of Arang Valley, District Bajaur, Khyber Pakhtunkhwa, Pakistan: a mountainous region of the Hindu Kush Range - Haq, Aminul; Badshah, Lal; Hussain, Wahid; Ullah, Irshad (Ethnobotany Research and Applications, 2023)
Background. Globally, humans traditionally use plants for the treatment of a variety of diseases. To document ethnomedical knowledge and practices, the remote Arange Valley of district Bajaur is still unexplored. The current study is a contemporary assessment that established the local knowledge of medicinal plants in the area. Methods. The area has diverse natural flora, and the local people rely on it for a variety of things, including traditional medicine. Semi-structured questionnaires were used in conjunction with direct interviews with 166 experienced persons to elicit ethnomedical information. The collected data were analyzed quantitatively for relative frequency citation (RFC), fidelity level (FL) and use value (UV). Results. It was recorded that 77 plant species from 46 families were being used in traditional medicine to treat a wide range of diseases. Lamiaceae with 11 species, was the most frequently utilized family, followed by Fabaceae with 5 species, Asteraceae, Polygonaceae, and Rosaceae, each with 4 species, one, two, or three species were contributed by the rest of the families. The distribution of habits included herbs (62.3%), shrubs (22.1%), and trees (13%) while lianas and parasites each made up 1.3%. Among the plant parts used in the production of remedies are leaves (39%), fruits, and roots (16% each), seeds, and the entire plant (8%) as well as rhizomes and areal stems with branches (4% each). Most medications are being used orally (68.97%) and topically (24.14 %) to treat chronic illnesses such as gastrointestinal problems, pulmonary infections, diabetes, kidney stones, urogenital tract infections and nerve stimulation. The quantitative analysis showed that the Berberis lycium and Sideroxylon mascatense have maximum RFC values i.e., 0.24 and 0.19, respectively used as a tonic, while Decaspermum blancoi exhibits an RFC value of 0.17 which is used for digestive disorders. The highest use values were recorded (1.0) for Sideroxylon mascatense and (0.78) for Berberis lycium. Conclusion: This study demonstrates that the area has a rich flora of medicinal plants and could be contributed to ethnobotanical knowledge. The data collected will serve as a basis for the comprehensive investigation of active molecular constituents of the medicinal flora of the area. Novel herbal medications in the field of pharmacology may soon be discovered via the investigation of these medicinal plants. Keywords: Ethnomedicinal uses, Indigenous knowledge, Natural compounds, Bajaur